(835) On Estimating Lot Size for a Variable Life Time Stock Items حول تقدير حجم الكمية بالنسبة لعناصر المخزون المتغير مدى الحياة - EL-SHAFEI, W.A.M.; ABD EL RAZEK, A.H. (INP, 2024)
We want to estimate the number of micrometers to be kept in stock to fulfill inspection needs for a period of five years, assuming: We always need 12 micrometers in simultaneous operation. The lifetime of the micrometers is not fixed, and the probable lives of the items are based on past experience